PURIFICATION BY FILTRATION OF SATURATED ETHANOLAMINES FROM HEAT-RESISTANT SALTS AND DEGRADATION PRODUCTS - Turaev Tolib Bozorovich; Bozorova Gavhar; Eshankulov Nurbek; Dushamov Alimbay (European Science Publishing, 2024)
The article presents the results of studies on purification of aqueous solutions of spent saturated ethanolamines from heat-resistant salts of destruction products by the filtration method. The work studied the process of purification of ethanolamines by three-stage filtration (sand, coal - bentonite and anionite (Tulsion (USA) A-23 and AB-17-8 RF strongly basic anionites of the gel type)) was recognized as the most effective method, and their properties were analyzed.
Keywords: ethanolamine, natural gas, hydrogen sulfide, carbon dioxide, absorbent, diethanolamine (DEA) and methyldiethanolamine (MDEA), destruction, anions, sand, activated carbon, mechanical compounds, heat resistant salts.